Use of an upright power wheelchair in spinal cord injury: a case series - Hong, Eunkyoung; Elliott, Michael; Kornfeld, Stephen; Spungen, Ann M. (Frontiers in Rehabilitation Sciences, 2024)
Objective: To explore independence, usability, and self-reported quality of life (QOL) in eligible persons with spinal cord injury (SCI) who used a standing powered wheelchair over a 12-week period. Setting: VA SCI research facility. Participants: Four participants with chronic SCI who use a wheelchair as the primary means of mobility. Intervention: A standing power wheelchair was used three times a week (3.5 hours/session) for 12 weeks in a supervised setting. Main Outcome Measures: safety, usability and feasibility, blood pressure in seated and standing positions, bowel, bladder, and pain item banks from the SCI-QOL Physical-Medical-Health domain, and overall user satisfaction with the device. Results: Participants consistently maintained normal blood pressure responses between seated and standing positions throughout the training sessions and learned to perform all the mobility tasks safely and independently. Participants reported improvements on the SCI-QOL and were generally satisfied with the upright standing power wheelchair. Conclusions: In this small case series of chronic, non-ambulatory individuals with SCI, the standing powered wheelchair was shown to be safe and efficacious.